The Effects of Beta Blocker (Metoprolol) & Calcium Channel Blockers (Amlodipine) on Serum Uric Acid Levels in the Patients of Hypertension - Narindar Kumar, Shirjeel Husain, Zeeshan Ul Haque, Abdul Aleem, Fazeela Rizwan, Muhammad Ishaque Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Hypertension is one of the leading health hazards which increases cardiovascular mortality and morbidity all over the world. Hyperuricemia associated with hypertension can cause the development of gout, especially in the female gender. Different antihypertensive drugs have different effects on serum uric acid levels. Aims & Objective: To compare the effects of beta blockers (metoprolol) and calcium channel blocker (amlodipine) on serum uric acid level I the patients of hypertension. Methodology: This study was conducted at the Medical OPD of Bhittai Dental & Medical College Mirpurkhas from July 2021 to December 2021. A total of 100 hypertensive patients were selected under inclusion and exclusion criteria and divided into two groups with equal numbers of patients. Group A patients used beta blockers (metoprolol) and group B patients used calcium channel blockers (amlodipine) for the treatment of hypertension for three months' duration. Serum uric acid was measured by the PAP uricase method before the start of treatment and after completion of the treatment research phase. Statistical analysis was done by SPSS version 22. Results: The mean serum uric acid level of male patients in group A was 7.4± 0.4 mg/dl and that of female patients in group A was 6.2± 0.1 mg/dl before the start of research. After three months of complete treatment phase, the mean serum uric acid level of male patients in group A was 7.1± 0.35 mg/dl and that of female patients in group A was 6.0 ± 0.31 mg/dl. The mean serum uric acid level of male patients in group B was 7.2± 0.38 mg/dl and that of female patients in group B was 6.1± 0.28 mg/dl before the start of research. After three months of the complete treatment phase, the mean serum uric acid level of male patients in group B was 7.0± 0.22 mg/dl and that of female patients in group B was 5.91± 0.27 mg/dl. There was no significant change in serum uric acid observed in either group under study. Conclusion: This study concluded that metoprolol (beta blocker) or amlodipine (calcium channel blocker) have no significant effect on serum uric acid levels in hypertensive patients.